Volvariella polysaccharides: isolation, structural characterization and structure-activity relationship: a review - Lin Guo; Jie Wang; Hui Liu; Huanjie Zhang; Fathy M.S.A. Mehaya; Changyang Ma (Journal of Future Foods)
In recent years, Volvariella polysaccharides (VPs) have been confirmed with various of biological activities, which can be used as the main ingredients of functional foods. It was reported to treat various diseases and disorders in humans, and have high nutritional and pharmaceutical significance. This paper summarized the latest progress in the extraction, separation and purification technologies, structure-activity relationship and action mechanisms of VPs, as well as the challenges, limitations during the application that may become the future direction.